Upaya Pencegahan Terhadap Pencemaran Lingkungan Hidup Akibat Kegiatan Usaha Bengkel di Kelurahan Sumerta - I Putu Devha Surya Wibawa; I Ketut Kasta Arya Wijaya; Ketut Adi Wirawan (Warmadewa Press, 2024)
The high population correlates with the level of pollution that occurs, considering the high level of mobility of each person makes the need for transportation facilities even greater. The existence of so many workshops affects the surrounding environmental conditions. The formulation of the issues raised is (1) How are the legal protection efforts against the environment from pollution due to workshop business activities in Sumerta Village?, (2) What are the obstacles in environmental protection due to workshop business activities in Sumerta Village? This thesis research uses empirical legal research methods. The results of the study found that there were prevention efforts made to the environment from pollution due to workshop business activities, namely by conducting socialization from the Environment and Hygiene Service and Sumerta Village to workshop business actors. Obstacles in enforcing environmental protection due to workshop business activities in Sumerta Village there are several factors such as factors of legal facilities, law enforcement officials, facilities and facilities, licensing, public legal awareness of the environment, and a large number of workshops and even distribution make supervision difficult.